Atrial natriuretic peptide predicts disease progression and digital ulcers development in systemic sclerosis patients. Issue 11 (November 2019) - Romaniello, Antonella; Rubattu, Speranza; Gigante, Antonietta; Simonelli, Francesca; Grimaldi, Maria C.; D'Angelo, Adriano; Alunni, Danilo; Sada, Lidia; Gasperini, Maria L.; Marchitti, Simona; Volpe, Massimo; Rosato, Edoardo
Abstract : Aims: Systemic sclerosis (SSc) is an autoimmune disease characterized by micro/macrovascular damage due to the underlying fibrosis. Markers able to predict the progression of cardiovascular damage, including digital ulcers, in SSc are warranted. We aimed at characterizing the relevance of N-terminal proatrial natriuretic peptide (NT-proANP) and N-terminal probrain natriuretic peptide plasma levels in relation to cardiovascular damage and digital ulcers in a cohort of Italian SSc patients. Methods: Seventy patients were enrolled (64 women and six men; mean age 56.7 ± 14 years) with a disease duration of 11.1 ± 8.3 years. Clinical, instrumental (nailfold videocapillaroscopy, ECG, transthoracic echocardiography, pulmonary function test with diffusion lung CO), NT-proANP and N-terminal probrain natriuretic peptide plasma levels measurement were performed at baseline. The clinical follow-up lasted 24 months. The statistical approach used to achieve the study objectives included multivariate analysis, receiver operating characteristic curve, Kaplan–Meier and Cox regression analyses. Results: Both NT-proNPs levels correlated with systolic pulmonary arterial pressure, but only the NT-proANP level correlated with right heart dimension. Both NT-proNPs levels were higher in patients experiencing events at follow-up but only the NT-proANP level significantly predicted the progression of cardiovascular damage, including development of pulmonary arterial hypertension (PAH). NT-proANP levels were higher in patients with digital ulcers and strongly predicted their development. Conclusion: Our results show that the NT-proANP plasma level significantly correlates with disease progression such as new onset of PAH, worsening of pulmonary hypertension and development of digital ulcers in a cohort of SSc Italian patients. If future studies will confirm our findings, the plasma NT-proANP level could be used in clinical practice as a novel sensitive marker for PAH and digital ulcers development in SSc.